Exploring the School Environment Through an Ethnomathematics Approach - Asih, Rizqi Retno; Nuzulah, Unsiyah; Purnomo, Purnomo (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Mathematics is often perceived as abstract and disconnected from everyday life, causing students to struggle with topics requiring symbolic representation, such as matrices. This situation indicates the need for learning approaches that connect formal concepts with real experiences, highlighting the urgency to address students’ limited ability to link symbolic representations with real contexts. This study aims to describe the process and results of exploring the school environment as a source of mathematical representation for matrix topics through an ethnomathematics approach. This research employed a qualitative approach with a case study design. Participants included one mathematics teacher and two 11th-grade students from SMA Negeri 1 Tengaran. Data were collected through observation, interviews, and documentation; instruments consisted of observation sheets, interview guides, and student worksheets (LKPD). Data analysis used the Miles, Huberman, and Saldana model with technique and source triangulation to enhance credibility. The results indicate that environmental exploration helped students identify real-world patterns representable as matrices, such as flowerpot arrangements, floor patterns, and school artwork. The findings also show contributions to mathematical literacy and the Pancasila Student Profile dimensions particularly critical thinking, creativity, and collaboration. The novelty of this study lies in integrating ethnomathematics into algebra topics (matrix concepts), which are rarely examined, and utilizing a modern school environment as a local context. Implications for teaching include replicating exploration steps such as field observation, pattern recording, and matrix representation to support routine lessons or other topics requiring connections between real objects and mathematical structures.